Unveiling the Power of Intellectual Capital in Driving Financial Performance: A Deep Dive into the IT Sector - Suzan Dsouza; Layal Kallach; Rezart Demiraj; Syed Faizan Hussain Zaidi (Ital Publication, 2026)
This study aims to theoretically and empirically investigate the relationship between intellectual capital (IC) and the financial performance of firms in the U.S. information technology (IT) sector, with a particular focus on Return on Assets (ROA) as a key performance indicator. Data were collected from 345 publicly listed IT companies over the period 2011–2022, yielding 1,792 firm-year observations. The research employed descriptive statistics, correlation matrices, box plot analyses, and multiple regression models to examine the effects of IC and its components, human capital efficiency, structural capital efficiency, and capital employed efficiency on financial outcomes. The analysis revealed that, contrary to conventional expectations and prior literature, IC exhibited a negative and statistically significant association with financial performance, highlighting potential inefficiencies in the utilization of intangible assets within the IT industry. These findings underscore the complexity of translating investments in IC into measurable financial gains, suggesting that firms may be overinvesting or misallocating resources in areas that do not yield immediate profitability. The novelty of this research lies in uncovering an unexpected inverse IC-performance link in a knowledge-intensive sector, thereby offering executives and policymakers new insights into how IC strategies should be re-evaluated and aligned with long-term value creation.